Factors Assosiated to Midwives' Knowledge Related to Complementary Therapies as an Effort to Provide Holistic Care in Reproductive Health Services in the Cirebon Region - Widayanti, Wiwin; Nur Aliah; Siti Difta Rahmantika; Eka Ratnasari; Yeni Fitrianingsih (Journal for Quality in Public Health, 2023)
The paradigm shift in midwifery services and the global situation towards the increasing demand for complementary practice requires midwives to have comprehensive knowledge of complementary therapies to integrate complementary and conventional midwifery services. The purpose of this study was to determine the factors related to midwives' knowledge of complementary therapies as an effort to provide holistic care for reproductive health services in the Cirebon Region. This research is a correlative analytical research, cross sectional approach. The respondents were midwives in the Cirebon Region. The sample size was 216 respondents. Sampling using purposive sampling. The data was analyzed with a chi-square test. The research instrument uses questionnaires that have been tested for validity and reliability. The results showed that there was significant assosiation between education, complementary training history, and information sources with complementary related knowledge, each with a p value of 0.000. There was no significant assosiation between the age of midwives, and the periode of working of midwives with complementary related knowledge with p values of 0.75 and 0.50 respectively. Midwives are expected to improve knowledge and skills based on evidence-based practice related to complementary therapies actively through available information sources, in an effort to provide excellent service to reproductive health holistically.